Neurotoxicity in the treatment of Parkinson's disease - N. Ya. Siritsa (Izdatelstvo OKI, 2023)
Currently, there is no neuroprotective therapy for the treatment of Parkinson's disease (PD), which would slow down the progression of the pathological process and prevent the development of the neurodegenerative process. The applied symptomatic therapy does not give a positive eﬀect. In this paper, an overview of antiparkinsonian medications that are used in the treatment of PD is made. These drugs give side eﬀects, causing neurotoxicity, while chemical agents, i.e. oxygen radicals have an adverse eﬀect on the structure or function of the central or peripheral nervous system.